The Relationship of Organizational Climate in Jop Satisfaction for Nurses - شعبان خضر; علاء طويل (Latakia University Journal -Medical Sciences Series, 2024)
"The organizational climate is considered a crucial element for achieving alignment between the organization’s goals and those of its employees. It directly influences the organization’s ability to succeed in its objectives efficiently and effectively, as well as the attitudes and behaviors of its members. Job satisfaction is one of the key factors determining the success or failure of organizations due to its negative impact, such as a decline in service quality, increased conflicts, high turnover, absenteeism, decreased motivation, and overall job dissatisfaction. This study aimed to examine the relationship between organizational climate and job satisfaction among nurses at Tishreen University Hospital in Latakia. The study adopted a descriptive correlational approach and used a questionnaire as a data collection tool, involving a sample of 420 nurses, representing 30% of the target population. The study revealed a statistically significant strong relationship between organizational climate and job satisfaction among nurses at Tishreen University Hospital. The study recommends that hospital management continues to focus on human resources, assesses nurses’ job satisfaction levels for continuous improvement, and reviews the rewards and compensation system to incorporate both motivational and material incentives."